Are the three hydroxyphenyl radical isomers created equal? – The role of the phenoxy radical –. Issue 44 (26th October 2015) - Hemberger, P.; da Silva, G.; Trevitt, A. J.; Gerber, T.; Bodi, A.
Abstract : Hydroxyphenyl radicals (˙C6 H4 –OH) rearrange in a heated micro tubular reactor to phenoxy (C6 H5 –O˙) radicals, which subsequently decompose to yield cyclopentadienyl and CO. Abstract : We have investigated the thermal decomposition of the three hydroxyphenyl radicals (˙C6 H4 OH) in a heated microtubular reactor. Intermediates and products were identified isomer-selectively applying photoion mass-selected threshold photoelectron spectroscopy with vacuum ultraviolet synchrotron radiation. Similarly to the phenoxy radical (C6 H5 –O˙), hydroxyphenyl decomposition yields cyclopentadienyl (c-C5 H5 ) radicals in a decarbonylation reaction at elevated temperatures. This finding suggests that all hydroxyphenyl isomers first rearrange to form phenoxy species, which subsequently decarbonylate, a mechanism which we also investigate computationally. Meta - and para -radicals were selectively produced and spectroscopically detectable, whereas the ortho isomer could not be traced due to its fast rethermalization and rapid decomposition in the reactor. A smaller barrier to isomerization to phenoxy was found to be the reason for this observation. Since hydroxyphenyl species may be present under typical sooting conditions in flames, the resonantly stabilized cyclopentadienyl radical adds to the hydrocarbon pool and can contribute to the formation of polycyclic aromatic hydrocarbons, which are precursors in soot formation.